2014
DOI: 10.1002/ange.201409928
|View full text |Cite
|
Sign up to set email alerts
|

Highly Diastereoselective and Enantioselective Olefin Cyclopropanation Using Engineered Myoglobin‐Based Catalysts

Abstract: Using rational design, an engineered myoglobin‐based catalyst capable of catalyzing the cyclopropanation of aryl‐substituted olefins with catalytic proficiency (up to 46 800 turnovers) and excellent diastereo‐ and enantioselectivity (98–99.9 %) was developed. This transformation could be carried out in the presence of up to 20 g L−1 olefin substrate with no loss in diastereo‐ and/or enantioselectivity. Mutagenesis and mechanistic studies support a cyclopropanation mechanism mediated by an electrophilic, heme‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
78
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 38 publications
6
78
1
Order By: Relevance
“…2b for the cyclopropanation of β -methylstyrene 3 with ethyl diazoacetate 4 (EDA). In agreement with literature reports 10 , Fe-PIX enzymes did not catalyse this reaction (Fig. 2b).…”
Section: Letter Researchsupporting
confidence: 93%
See 1 more Smart Citation
“…2b for the cyclopropanation of β -methylstyrene 3 with ethyl diazoacetate 4 (EDA). In agreement with literature reports 10 , Fe-PIX enzymes did not catalyse this reaction (Fig. 2b).…”
Section: Letter Researchsupporting
confidence: 93%
“…In particular, mutants of Physeter macrocephalus myoglobin (Myo) and Bacillus megaterium cytochrome P450 BM3h (P450) with and without an mOCR stability tag were overexpressed in high yields and purified (up to 70 mg l −1 of protein; Fig. 1a, Supplementary Tables 1 and 2) 9, 10,27 . Circular dichroism spectroscopy revealed that these apo-proteins retain the fold of their native Fe-PIX analogues (Fig.…”
mentioning
confidence: 99%
“…Fasan's group recently reported that myoglobin, which naturally uses histidine as the axial ligand to the iron-heme, can also be engineered for cyclopropanation (Bordeaux et al 2015), at least in vitro. Both labs have now demonstrated that optimized cyclopropanating enzymes catalyze tens of thousands of turnovers for various olefins, with substrate range and product selectivity that are tunable by protein engineering (Bordeaux et al 2015;Coelho et al 2013b).…”
Section: New Enzymes From Old: Adding To the Cytochrome P450's (Alreamentioning
confidence: 99%
“…Both labs have now demonstrated that optimized cyclopropanating enzymes catalyze tens of thousands of turnovers for various olefins, with substrate range and product selectivity that are tunable by protein engineering (Bordeaux et al 2015;Coelho et al 2013b). The P450-derived enzyme functions very well in whole bacterial cells, where a His-ligated variant has been used for preparative-scale synthesis of a pharmaceutical intermediate (Wang et al 2014a).…”
Section: New Enzymes From Old: Adding To the Cytochrome P450's (Alreamentioning
confidence: 99%
“…Up to 40 000 TTN were obtained at higher substrate or lower catalyst loadings (see Figure S4 in the Supporting Information), which places P411-VAC cis among the most active carbene transfer hemoproteins described to date. 31,33,44 For the trans-selective variant P411 BM3 -CIS I263G L437F, further site-saturation mutagenesis and screening yielded variant P411 BM3 -CIS I263G L437F V87L L181R, which we term P411-VAC trans . In whole E. coli cells, this variant catalyzes cyclopropanation of N-vinylphthalimide with EDA in 86% yield with 980 TTN, 3:97 dr, and 92% ee ( Figure 1B).…”
mentioning
confidence: 99%